Perancangan sistem dan prosedur penjualan tunai di Toko J LU Fashion Manado - Paat, Victoria Maria; Pontoh, Winston; Pinatik, Sherly (Manajemen Bisnis dan Keuangan Korporat, 2025)
Despite the integration of technology in sales management systems, many businesses still rely on manual cash sales systems and procedures. This study aims to address this by examining the cash sales system and procedures at J LU Fashion Store. The research method used is a qualitative approach with data collection techniques, including interviews, observations, and documentation. The results are clear: at J LU Fashion Store, the cash sales accounting information system, financial calculations, and sales records are still all done manually. There are no guidelines or SOPs to help the company, meaning the sales process in the store is not optimal.